An adaptive choice of smoothing width in statistical estimation of distribution density - Kavaliauskas, Mindaugas (Lietuvos matematikos rinkinys, 1997)
This article illustrates the adaptive kernel probability density function estimation method, shows encounted problems, gives solutions and suggestions. The simulation results are discussed.